Incidence and characteristics of neurotoxicity in immune checkpoint inhibitors with focus on neuromuscular events: Experience beyond the clinical trials. Issue 2 (24th March 2020) - Bruna, Jordi; Argyriou, Andreas A.; Anastopoulou, Garifallia G.; Alemany, Montse; Nadal, Ernest; Kalofonou, Foteini; Piulats, Josep M.; Simó, Marta; Velasco, Roser; Kalofonos, Haralabos P.
Abstract: Immune checkpoint inhibitors (ICIs) are associated with various neurological adverse events (NAEs). We herein explored the incidence and clinical phenotype of immune‐related NAEs in cancer patients. Medical records of ICI‐treated cancer patients were reviewed between the years 2010 and 2018, with an aim to characterize immuno‐related NAEs. A total of 1185 ICIs‐treated patients were identified, 63.7% of which were males and 36.3% were females, with a mean age of 63.4 ± 7.3 years. Twenty‐four from the overall ICIs‐treated patients (2%) developed NAEs. No differences were identified in terms of age, sex, tumor type and class of ICIs between the patients who developed NAEs and those who did not. The median number of cycles of ICI treatment before NAEs onset were 4.5 (1‐10), and the median time was 102 days. Peripheral nervous system (PNS) involvement was present in 14 patients (58.4%) and central nervous system (CNS) involvement in 10 (33.3%), including 2 patients with aseptic meningitis and polyradicular involvement. Amongst PNS complications, there were five (20.8%) with axonal sensory neuropathies, four (16.7%) with Guillain‐Barre‐like syndromes, and four (16.7%) with myositis and/or myasthenic syndromes. The majority of patients with PNS‐related NAEs (n = 11; 78.6%) improved after ICIs discontinuation and treatment with immune‐modulating therapies. The time to neuromuscular toxicities onset was significantly shorter, compared to CNS NAEs (median 70 vs 119 days, P = .037). Immune‐related NAEs mostly present with neuromuscular complications. Discontinuation of ICIs and appropriate treatment should be commenced early throughout the process, in order to maximize a favorable outcome.